2004
DOI: 10.1007/s00259-004-1611-0
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of 3?-deoxy-3?-[18F]fluorothymidine into L5178Y tumours in vivo is dependent on thymidine kinase 1 protein levels

Abstract: This study shows that in vivo [18F]FLT kinetics depend on TK1 protein expression. ATP may be important in realising this effect. Thus, [18F]FLT-PET has the potential to yield specific information on tumour proliferation in diagnostic imaging and therapy monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 26 publications
1
67
1
2
Order By: Relevance
“…FLT transport and uptake is not entirely dependent on the activity of thymidine kinase 1 (TK1) alone, but ATP may also act as an important cofactor [11,12]. The primary cancers in this study were all of moderate size or greater, and there may have been a paucity of available ATP leading to suboptimal modulation of TK1.…”
Section: Discussionmentioning
confidence: 98%
“…FLT transport and uptake is not entirely dependent on the activity of thymidine kinase 1 (TK1) alone, but ATP may also act as an important cofactor [11,12]. The primary cancers in this study were all of moderate size or greater, and there may have been a paucity of available ATP leading to suboptimal modulation of TK1.…”
Section: Discussionmentioning
confidence: 98%
“…Barthel et al reported that in vivo uptake of 18 F-FLT is closely related to thymidine kinase 1 activity and the cellular concentration of adenosine triphosphate (32). However, FIGURE 4.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FLT acts as a chain terminator and is only marginally incorporated into DNA and therefore not a direct measure of proliferation (22). In vitro studies indicate that 18 F-FLT uptake is closely related to thymidine kinase 1 activity and respective protein levels (35), as well as to expression of nucleoside transporters in the cellular membrane (36). 18 F-FLT is considered to reflect thymidine kinase 1 activity and, hence, S-phase fraction rather than DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%